Interactions of Dietary and Waterborne Copper in Rainbow Trout, Oncorhynchus Mykiss - Kamunde, Collins N. (My University, 2002)
In mammals, copper is an essential yet potentially toxic trace element if accumulated in excess of cellular requirements. These conflicting properties demand a tight regulation of Cu, both at the cellular and organismal levels. Unlike mammals, fish can assimilate significant amount of Cu from the water via the gills, in addition to the dietary uptake via the gastrointestinal tract. The relative contributions of branchial and gastrointestinal routes of uptake in Cu homeostasis and toxicity in fish remain largely unknown. Therefore this thesis examined the interactions between dietary and waterborne routes of Cu uptake as they relate to homeostasis and toxicology of Cu using the freshwater rainbow trout, Oncorhynchus mykiss, as a model system.
Copper is clearly essential to fish based on both growth response and body Cu status in rainbow trout. Direct measurements of unidirectional Cu uptake following exposure of rainbow trout to conditions depleted and elevated in Cu showed up-regulation and down regulation of branchial Cu uptake, respectively. Thus Cu uptake from the water responds to body Cu status and there is an inteaction between dietary and waterborne Cu uptake in the maintenance of body Cu balance. Under conditions of background water and dietary Cu levels, diet is the more important route of Cu uptake, accounting for about 90% of the Cu intake. However, during deficiency, waterborne Cu uptake may contribute up to 60% of the Cu requirement. Interestingly, while waterborne Cu uptake responds to acclimation to elevated waterborne Cu, as well as elevated dietary Cu, gastrointestinal Cu uptake does not. It thus appears that the gut serves for bulk acquistion of Cu while the gill performs homeostatic fine-tuning via adjustment of branchial Cu transport mechanisms. Moreover, the response of branchial uptake mechanisms to Cu acclimation suggests the presence of at least two types of Cu transporters at the gill epithelium.
A linkage between Cu and sodium (Na+) uptake and homeostatic mechanisms in fish gills was unveiled. Elevating dietary Na+ reduced unidirectional uptake rates of Cu, and up to 95% of the reduction in Cu uptake was explained by parallel reduction in waterborne Na+ uptake. This co-variation between Na+ and Cu uptake strongly suggests that Cu and Na+ share uptake pathways, possibly the apical Na+ channel. Furthermore, long-term exposure to elevated dietary Na+ reduced Cu accumulation in the liver as well as the short-term binding of Cu to the gills. These findings have important implications including the use of dietary Na+ to protect against Cu toxicity both im fish and humans.
From a toxicological perspective, this thesis research uncovered new areas for consideration in the development of water quality criteria for Cu. One method currently under development for determining realistic site-specific water quality guidelines is the Biotic Ligand Model (BLM). The US Environmental Protection Agency has provisionally adopted the BLM as a site-specific modification to the current acute Ambient Water Quality Criteria for Cu. The tenet of BLM is prediction of the metal bound to the gill that results in toxicity in water of known chemistry. Several water chemistry parameters including Ca2+, Na+, dissolved organic matter, and pH greatly modify metal binding to the gill and hence toxicity. This thesis shows that dietary quality factors such as Cu and Na+ content, and acclimation to waterborne Cu influence the binding of Cu to the gill biotic ligand. Future development of the BLM should therefore consider dietary factor and acclimation effects.
Lastly, this thesis provides direct evidence that dietary metal uptake and diet quantity are important in toxicology and environmental risk assessment for metals. Food quantity influences fish growth and metal uptake thereby affecting whole body and tissue Cu concentrations such that lower Cu concentrations do not necessarily reflect lower Cu accumulation but can, in fact, represent growth dilution. Therefore, using body metal burdens for biomonitoring and risk assessment is meaningful only if dietary metal intake and feeding regimes are taken into account.
Keywords: Biology; Biology